Effect of Aqueous Extract of Crocus sativus L. on Morphine-Induced Memory Impairment - Sayede Maryam Naghibi; Mahmoud Hosseini; Fatemeh Khani; Motahare Rahimi; Farzaneh Vafaee; Hassan Rakhshandeh; Azita Aghaie (Hindawi Limited, 2012)
In the present study, the effect of aqueous extracts of saffron on morphine-induced memory impairment was investigated. On the training trial, the mice received an electric shock when the animals were entered into the dark compartment. Twenty-four and forty-eight hours later, the time latency for entering the dark compartment was recorded and defined as the retention trial. The mice were divided into (1) control, (2) morphine which received morphine before the training in the passive avoidance test, (3-5) three groups treated by 50, 150 and 450 mg/kg of saffron extract before the training trial, and (6 and 7) the two other groups received 150 and 450 mg/kg of saffron extract before the retention trial. The time latency in morphine-treated group was lower than control (P < 0.01). Treatment of the animals by 150 and 450 mg/kg of saffron extract before the training trial increased the time latency at 24 and 48 hours after the training trial (P < 0.05 and P < 0.01). Administration of both 150 and 450 mg/kg doses of the extract before retention trials also increased the time latency (P < 0.01). The results revealed that the saffron extract attenuated morphine-induced memory impairment.